PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL ACTIVITY OF Zingiber officinale AND Syzygium aromaticum ON BACTERIA PATHOGENS ISOLATED FROM KUNUN-AYA - HANIFA, MUHAMMED; AMINU, BUKAR; HUSSEINI JOSHUA, AKAWU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The increased use of antibiotics in agricultural practices is accompanied with the development of resistant foodborne pathogens. Spices and herbs have been reported to be potent source of natural antioxidants. This study aimed to assess the antibacterial activity of Zingiber officinale (Ginger) and Syzygium aromaticum (Clove) against bacterial food pathogens. Fresh ginger and clove were collected, identified, air dried and extracted the bioactive compound using distilled water. The extract was used for phytochemical analysis of flavonoids, tannins, saponins, steroids, glycosides, alkaloids and total phenols and determination of inhibition zone. Bacteria and fungi were isolated and identified from locally prepared Pap (Kunun aya) and later used for the antimicrobial analyses. Phytochemical screening shows clove contain flavonoids, tannins, saponins, steroids, glycosides, alkaloids and total phenols whereas glycosides and tannins were absent in ginger. Ginger has more antibacterial activity with the highest zone of inhibition observed in E coli at 16.73mm at 2000µg and the lowest in Salmonella at 13.83mm at 2000µg, clove also shows antibacterial activity with the highest zone of inhibition (14.8mm) in S. aureus at 2000µg and the lowest 11.5mm in E. coli at 2000µg. Thus, from the result obtained, it can be concluded that Zingiber officinale and Syzygium aromaticum extracts possesses effective antimicrobial agents against food pathogens.